Contribuição ao conhecimento dos poliplacóforos do Estado do Rio de Janeiro, Brasil (Mollusca; polyplacophora) - Guerra Junior, Orlando (1978)
Eleven species of chitones distributed by five genera belonging to the families Lepidopleuridae, Ischnochitonidae and Chaetopleuridae, all from the coast of the state of Rio de Janeiro, Brazil, are studied in this work. The taxonomic and morphological aspects are emphazised, aside from observations on geographic distribution and habitat.